How to think about money - Clements, Jonathan; Bernstein, William J. (Ascent Audio, 2020)
There are those who think the goal of investing is to beat the market and amass as much wealth as possible, that street smarts and hard work ensure investment success, and that the road to happiness is paved with more of everything. And then there are those who get it. Want a more prosperous, less stressful financial life? Jonathan Clements, longtime personal finance columnist for The Wall Street Journal, is here to help. His goal: to provide readers with a coherent way to think about their finances, so they worry less about money, make smarter financial choices and squeeze more happiness out of the dollars that they have. How to Think About Money is built around five key ideas: - Money can buy happiness, but we need to spend with great care. - Most of us will enjoy an extraordinarily long life--and that has profound financial implications. - We are hardwired for financial failure, so sensible money management takes great mental strength. - We need to bring order to our financial life--by focusing on our paycheck, or lack thereof. - If we want to add to our wealth, we should strive to minimize the subtractions. "Now why didn't I think of that? That's what you'll ask yourself after you read Jonathan Clements's fine new book. Its beauty lies in the commonsense and wisdom that is summed up in just five simple steps that will help you to earn your financial independence. Easy to understand, essential to follow."--John C. Bogle, founder, The Vanguard Group
Online resource; title from title details screen (O'Reilly, viewed February 28, 2023)
Keywords: Finance, Personal; Audiobooks; Livres audio